Back door Java : state formation and the domestic in working class Java - Newberry, Janice C. (Broadview ethnographies & case studies., 2006)
"In the densely populated urban neighbourhoods of Java, women manage their houses and their communities through daily exchanges of food, childcare, and labour. Their domestic work is based on local ideas of community cooperation and support, but also on the Indonesian government's use of women as unpaid social workers. Consequently, women are a pivotal point in both state-sponsored programs of domesticity and in the local practice of community exchange managed from individual houses. Back Door Java explores the everyday lives of ordinary urban Javanese from a new perspective on domestic space and the state. Using rich ethnographic description of a neighbourhood in Central Java, Newberry illuminates the ways in which state rule is intimately connected to the household and the community."--Jacket